An evaluation of the wear behaviour of a dual-phase low-carbon steel - Aksoy, M; Karamis, MB; Evin, E (Elsevier Science Sa Lausanne, 1996)
Wear behaviour of dual-phase AISI 1020 steel was investigated. The steel was austenitized at critical transformation temperature and rapidly quenched. Thus, the structure of the steel consists of martensite and ferrite phases in different proportions. Heat treated samples were subjected to wear with a cylinder-on-cylinder sample configuration under dry sliding conditions. Wear resistance was determined as functions of hardness and proportion of martensite phase, and elongation of the steel. The wear resistance of the dual-phase 1020 steel was also compared with those of hardened and tempered AISI 1040 and 8640 steels. It was indicated that the wear resistance of the test steel decreases with martensite proportions, and increases with martensite hardness and elongation of the steel.
Keywords: dual-phase; martensite proportion; wear resistance; ferrite ductility; elongation